2016
DOI: 10.1109/temc.2016.2566449
|View full text |Cite
|
Sign up to set email alerts
|

Field-to-Long-Segmented-Trace Coupling With Arbitrary Loads and a Transparent Upper Bound Using a Single Modified Taylor Cell

Abstract: In modern electronic products, the printed circuit board (PCB) traces may well form the dominant coupling path in radiated immunity problems. Therefore, an understanding of the designable parameters that influence the worst-case induced voltages can be of use to the PCB designer, together with rapid simulations. Therefore, a modified single (unmeshed) Taylor cell is combined with transmission line theory to predict the terminal voltages induced by a grazing, vertically polarized plane wave, incident on a multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…The coupling of an incident plane wave to a PCB at the left of Figure 1b will be modeled with the Single Modified Taylor cell [5]. To allow for comparison with measurement on a GTEM cell, a simple model for the GTEM's imperfections will be added [6].…”
Section: Field-to-trace Coupling Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The coupling of an incident plane wave to a PCB at the left of Figure 1b will be modeled with the Single Modified Taylor cell [5]. To allow for comparison with measurement on a GTEM cell, a simple model for the GTEM's imperfections will be added [6].…”
Section: Field-to-trace Coupling Modelmentioning
confidence: 99%
“…For the case of a vertically polarized, grazing plane wave incident on a microstrip trace with characteristic loads, it has been shown that a single cell may suffice, modified by a correction factor for long line effects [8]. Basic transmission line theory can then by applied to take into account arbitrary loads [5].…”
Section: Field-to-trace Coupling Modelmentioning
confidence: 99%
“…For the simulation, a modified Taylor cell was used, which predicts the coupling of a vertically polarized, grazing incident plane wave to a multi-segment trace of constant characteristic impedance, with arbitrary terminal loads [2].…”
Section: A Test Casesmentioning
confidence: 99%
“…Therefore, additional proof was needed that the problem lie in the GTEM cell, and not in the model. A full-wave simulation was run, which closely resembled the simulation of the model [2]. Yet, still more proof was needed.…”
Section: Introductionmentioning
confidence: 99%